Negative pretransplant serostatus for Toxoplasma gondii is associated with impaired survival after heart transplantation - Dösch, Andreas; Ammon, Kerstin; Konstandin, Mathias; Celik, Sultan; Kristen, Arnt; Frankenstein, Lutz; Müller, Susanne; Sack, Falk-Udo; Katus, Hugo; Dengler, Thomas (Transplant international, 2010)
Chronic Toxoplasma gondii infection is known to trigger potentially adverse immunoregulatory changes, but limited data exist on long-term implications for heart transplant (HTX) recipients. We evaluated the risk of all cause mortality regarding T. gondii serostatus prior to HTX. Pre-HTX T. gondii serostatus was obtained in 344 recipients and 294 donors. Mean age was 52.1 ± 10.2 years and mean follow-up time after HTX was 5.7 (±5.5, median 3.5) years. All seronegative patients received prophylaxis with pyrimethamine/sulfomethoxazole or cotrimoxazol for 6 months after transplantation. Multivariate survival analysis adjusted for diabetes mellitus, pre-HTX renal function, recipient age, type of primary immunosuppression (i.e. HTX before 2001), cytomegalovirus (CMV) high-risk status, ischemic time, and number of treated rejection episodes was performed. Overall, 190 recipients (55.2% of total) were seronegative and 154 (44.8% of total) were seropositive for T. gondii prior to HTX. One hundred and fifty-two recipients died during follow-up (44.2% of total). Negative recipient Toxoplasma serostatus was associated with a significantly higher risk of all-cause mortality (P = 0.0213). Recipient T. gondii serostatus did not influence the number of cellular or humoral rejection episodes. Analyses of specific causes of death showed a trend toward a higher number of infection-related deaths in the seronegative subgroup (P = 0.13). No statistically significant effects of T. gondii donor/recipient seropairing, or seroconversion were observed. Negative preoperative serostatus for T. gondii in HTX recipients appears to be an independent risk factor associated with increased all-cause mortality. The cause of impaired survival in Toxoplasma seronegative recipients is currently unclear; possible explanations include an alteration of immune-reactivity/-regulation or adverse effects of prophylactic medication.